2013
DOI: 10.1021/jf4024195
|View full text |Cite
|
Sign up to set email alerts
|

Release of Small Phenolic Compounds from Brewer’s Spent Grain and Its Lignin Fractions by Human Intestinal Microbiota in Vitro

Abstract: Brewer's spent grain (BSG), the major side-stream from brewing, is rich in protein, lignin, and nonstarch polysaccharides. Lignin is a polyphenolic macromolecule considered resilient toward breakdown and utilization by colon microbiota, although some indications of release of small phenolic components from lignin in animals have been shown. The aim of this study was to investigate if the human intestinal microbiota can release lignans and small phenolic compounds from whole BSG, a lignin-enriched insoluble fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…Interactions of the very insoluble DF analysed here as a sum of SSM and SIM with colonic bacteria remain to be studied. We have previously shown that recalcitrant lignin-rich fractions of brewer's spent grain are to a small extent metabolised in an in vitro colon model to, for example, 4-methyl catechol ( 55 , 56 ), and ferulic acid together with its metabolites such as hydroxylated phenylpropionic and acetic acids ( 57 ) has been suggested to be one mediator of health effects of cereal DF ( 58 ). Bilberry phenolics are mainly anthocyanins, which can be converted to their specific benzoic acid derivatives ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions of the very insoluble DF analysed here as a sum of SSM and SIM with colonic bacteria remain to be studied. We have previously shown that recalcitrant lignin-rich fractions of brewer's spent grain are to a small extent metabolised in an in vitro colon model to, for example, 4-methyl catechol ( 55 , 56 ), and ferulic acid together with its metabolites such as hydroxylated phenylpropionic and acetic acids ( 57 ) has been suggested to be one mediator of health effects of cereal DF ( 58 ). Bilberry phenolics are mainly anthocyanins, which can be converted to their specific benzoic acid derivatives ( 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple classification systems have been suggested for dietary fibers (Institute of Medicine, 2001; Tungland and Meyer, 2002), the characteristics of solubility and fermentability have been proposed as the most appropriate classifications (Tungland and Meyer, 2002;Dhingra et al, 2012). Although many ingredients contain multiple types of fibers, Figure 2 highlights the range of solubility and fermentability that generally characterize common fiber sources used in the pet food industry (Iktor et al, 1989;Naran et al, 2008;Aura et al, 2013;McRorie, 2013;Azad et al, 2014;Chung et al, 2017;Gupta et al, 2018). The physical and chemical properties of the fiber, including particle size and bulk volume, surface area characteristics, and hydration properties determine accessibility of the fiber to microbial degradation, as well as the physiological effects of the fiber (Dhingra et al, 2012) and thus the metabolic fate of the fiber in the digestive tract (Dhingra et al, 2012).…”
Section: Complex Carbohydratesmentioning
confidence: 99%
“…In addition, it has been suggested that the intestinal microbiota, particularly Lactobacilli (e.g., L. salivarius , L. paracasei , L. rhamnosus ) and Bifidobacteria (e.g., B. adolescentis, B. breve , B. longum ), can partially degrade the lignin in BSG and metabolize the compounds released (Niemi et al 2013 ). More recently, partial lignin degradation mediated by human fecal microbiota was shown in a colon intestine model (Ohra-aho et al 2016 ; Aura et al 2013 ). Here, it was suggested that lactic acid bacteria can easily adapt in BSG-based broth, thus paving the way for the use of probiotic strains as starter cultures for further improvement of the bioactive properties of fermented BSG (Gupta et al 2013 ).…”
Section: Brewers’ Spent Grain In Human and Animal Dietsmentioning
confidence: 99%